Effectiveness of a Four-Stage Death Education Model Based on Constructivist Learning Theory for Trainee Nursing Students - Yang Y; Li Y; Fu J; Guo D; Xue J (Journal of Multidisciplinary Healthcare)
Yujing Yang,1,* Yue Li,2,* Jia Fu,3 Dan Guo,4 Jingjing Xue1 1Fundamental Nursing Teaching- Research Department, Fenyang College of Shanxi Medical University, Fenyang City, Shanxi Province, 032200, People’s Republic of China; 2Academic Affairs Office, Fenyang College of Shanxi Medical University, Fenyang City, Shanxi Province, 032200, People’s Republic of China; 3Department of Radiation Oncology, Shanxi Cancer Hospital, Taiyuan City, Shanxi Province, 030013, People’s Republic of China; 4Department of Research and Teaching, China Aerospace Science and Industry Corporation 731 Hospital, Beijing City, 100074, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yujing Yang, Fundamental Nursing Teaching- Research Department, Fenyang College of Shanxi Medical University, No. 16 Xueyuan Road, Fenyang City, Shanxi Province, 032200, People’s Republic of China, Tel +86 18335846366, Email yangyj2024yj@163.comObjective: To explore the effectiveness of the four-step death education model based on constructivist learning theory in enhancing the death coping abilities and attitudes of trainee nurses and improving course satisfaction.Methods: Sixty-six trainee nurses from a tumour hospital in Shanxi Province were selected as the study subjects, and a class-experimental research design was adopted, in which the nursing students before the course implementation were taken as the control group and those after the course implementation were taken as the experimental group. Death Attitude Profile Revised Scale (DAP) was used to measure the cognitive attitude of nursing students towards death, and a self-made questionnaire was used to test the satisfaction of nursing students with the curriculum design. Paired sample t test was used to compare the participants before and after the study.Results: Post-course death avoidance score, fear of death score, and escape-orientated death acceptance score of the trainee nurses (all P< 0.05) were higher than the control group. Neutral death acceptance score (P< 0.05) was lower amongst the trainee nurses than the control group after the course. It showed that the attitudes towards death of the trainee nurses before and after the course improved in terms of fear and anxiety, sense of avoidance, and neutral acceptance. In the evaluation of the content of the course, the teaching methods of the course, and the teaching results, most of the trainee nurses gave a better evaluation.Conclusion: The four-step death education model based on constructivist learning theory significantly improved the death coping skills and attitudes of trainee nursing students. Although this educational model is still limited, it provides research materials for the future establishment of a systematic death education.Keywords: constructivist learning theory, death education, placement, nursing students